Awardee Summary of 2023 Taiwan Oncology Society Clinical Research Award Recipient: Persistent Endeavors on Research of Digestive Cancers for Three Decades - Kun-Huei Yeh (Journal of Cancer Research and Practice)
Objective: Digestive cancers account for five of the top ten cancer-related deaths in Taiwan. Our team has made persistent endeavors in translational research and clinical trials of digestive cancers for almost three decades. Data Sources and Study Selection: We enrolled relevant translational and clinical studies for digestive cancers published by our groups in the past three decades. Results: First, we developed a unique weekly 24-h infusion of high-dose 5-fluorouracil (5-FU) and leucovorin regimen (HDFL) in 1992. HDFL exhibits satisfactory single-agent activity, minimal myelosuppression, and mild toxicity. A variety of HDFL-based doublet combinations (such as cisplatin-HDFL, oxaliplatin-HDFL, and paclitaxel-HDFL) have become cornerstone regimens for three decades for the treatment of gastric cancers, with high efficacy and manageable toxicity at our hospital. Second, we have made persistent efforts in translational research and clinical trials on early-stage gastric mucosa-associated lymphoid tissue lymphomas (MALTomas), gastric diffuse large B-cell lymphomas, colorectal cancers (CRCs), pancreatic cancers, and immuno-oncology. Third, on behalf of the Taiwan Oncology Society, we participated in and published the Pan-Asian adapted European Society for Medical Oncology (ESMO) Clinical Practice Guidelines for locally advanced and metastatic CRC, gastric, and esophageal cancers, and the consensus meeting on tumor-agnostic indications of microsatellite instability-high (MSI-H) and NTRK. Conclusion: In the future, our team will make persistent endeavors in research on digestive cancers for immunotherapy and precision medicine to further improve treatment outcomes.